Nāmadhārī itahāsa, arathāta, Jīwana srī satigurū Bālaka Siṅgha jī - Cakrawaratī, Indara Siṅgha (SAMP early 20th-century Indian books project, 1934)
Biography of Bālaka Siṅgha, 1785-1862, Sikh religious leader of Namdharis, Sikh sect.